SYNTHESIS OF ZEOLITE BETA DIRECTLY FROM RICE HUSK ASH: EFFECT OF REACTION COMPOSITION ON CRYSTALLINITY OF ZEOLITE BETA - Didik Prasetyoko; Zainab Ramli; Salasiah Endud; Halimaton Hamdan; Bogdan Sulikowski (Universitas Gadjah Mada, 2006)
White rice husk ash obtained from complete uncontrolled burning of rice husk contains more than 94% silica. The ash, which consists of crystalline silica of the type tridymite and α-crystobalite, was used directly as a source of silica in the synthesis of zeolite beta. The mole oxide ratio of the initial gel of 1.25-8Na2O: 10-120SiO2: Al2O3: 1-20TEA2O: 150-1000H2O was prepared and heated at 150°C in a static condition for 6 d. The solid phases formed were monitored by XRD technique. Influence of reaction mixture ratio in the initial gel to the crystalline products formed was studied. Results showed that the pure zeolite beta was formed in a certain range of reaction mixture, i.e.: 1.25-4Na2O : 15-45SiO2 : Al2O3 : 4-10TEA2O : 240-480H2O. The other ratio of reaction mixtures produced crystalline phases such as analcime, Na-P, mordenite, and gismondine, and non-reacted of α-crystobalite and tridymite.